Increased In Vitro Intercellular Barrier Function of Lung Epithelial Cells Using Adipose-Derived Mesenchymal Stem/Stromal Cells - Mitsutoshi Ishii; Tomoshi Tsuchiya; Ryoichiro Doi; Yoichi Morofuji; Takashi Fujimoto; Hideki Muto; Takashi Suematsu; Ryoichi Mori; Keitaro Matsumoto; Takuro Miyazaki; Koichi Tomoshige; Hironosuke Watanabe; et al. (MDPI AG, 2021)
With the emergence of coronavirus disease-2019, researchers have gained interest in the therapeutic efficacy of mesenchymal stem/stromal cells (MSCs) in acute respiratory distress syndrome; however, the mechanisms of the therapeutic effects of MSCs are unclear. We have previously reported that adipose-derived MSCs (AD-MSCs) strengthen the barrier function of the pulmonary vessels in scaffold-based bioengineered rat lungs. In this study, we evaluated whether AD-MSCs could enhance the intercellular barrier function of lung epithelial cells in vitro using a transwell coculture system. Transepithelial electrical resistance (TEER) measurements revealed that the peak TEER value was significantly higher in the AD-MSC coculture group than in the AD-MSC non-coculture group. Similarly, the permeability coefficient was significantly decreased in the AD-MSC coculture group compared to that in the AD-MSC non-coculture group. Immunostaining of insert membranes showed that zonula occuldens-1 expression was significantly high at cell junctions in the AD-MSC coculture group. Moreover, cell junction-related gene profiling showed that the expression of some claudin genes, including claudin-4, was upregulated in the AD-MSC coculture group. Taken together, these results showed that AD-MSCs enhanced the barrier function between lung epithelial cells, suggesting that both direct adhesion and indirect paracrine effects strengthened the barrier function of lung alveolar epithelium in vitro.